Apparent metabolizable energy and digestibility of quinoa (Chenopodium quinoa) seed in turkeys of 5 and 10 weeks of age - Paredes, Manuel (2023)
The aim of this study was to estimate the apparent metabolizable energy content and digestion coefficients of quinoa (Chenopodium quinoa) seed in turkeys of 5 and 10 weeks of age. Four diets were evaluated: starter basal (BI), BI +20% quinoa (BIQ), finisher basal (BF) and BF + 20% quinoa (BFQ) in two periods. In the first period, 12 Hybrid Converter male turkeys (initial weight = 601.2 g; age = 21 d) distributed in two dietary treatments (BI and BIQ) with 3 repetitions of 2 turkeys (2 birds per metabolic cage) were used. At 33, 34 and 35 days of age, consumption and excreta were controlled. In the second evaluation, 6 male turkeys from the original flock of 400 birds were used (weight = 3825.3 g; age = 56 d) and distributed in two dietary treatments (BF and BFQ) with 3 repetitions of 1 turkey each. At 68, 69 and 70 days of age, consumption and excreta were controlled. In the 5-week phase, the digestion coefficients of dry matter (DM), crude protein (PC), ethereal extract (EE), nitrogen-free extract (ELN) and apparent metabolizable energy (EMA) of the BIQ diet was greater (p<0.05) than the BI diet. However, in the 10- week group, the BFQ diet showed lower digestion coefficients (p<0.05) for PC, EE, and EMA than the BF basal diet. These results allowed determining the digestion coefficients and EMA of the quinoa seed ingested by turkeys of 5 and 10 weeks. The results indicate that quinoa seed in turkeys has a greater EMA, and greater DM, PC and EE digestion coefficients at 5 weeks than at 10 weeks of age.